PENGARUH MODEL PEMBELAJARAN SIMAYANG UNTUK MENINGKATKAN KETERAMPILAN METAKOGNITIF PESERTA DIDIK PADA MATERI STRUKTUR ATOM - Yani Apriyani (Jurnal Redox, 2019)
This research was motivated by the low metacognitive skills of students and teacher-centered learning interactions. The Simayang learning model can trigger students to be more active and use their thinking skills when learning in class. The purpose of this study was to determine the improvement of students' metacognitive skills by using the Simayang learning model on atomic structure material. This research is a quasi experimental study with a quantitative approach with the design of "pretestposttest non-equivalent control group". This research was conducted at SMAN 1 Ciwaru in Kuningan Regency in the 2018/2019 academic year. The sample of this research is class X IPA 1 as the experimental class and class X IPA 2 as the control class. Data collection was carried out using test questions and observation sheets. The results showed that the experimental class had better metacognitive skills than the control class when viewed from the posttest results and the observation sheet of metacognitive skills. The average posttest result for the experimental class was 84.91 while the control class was 64.08. The increase value obtained from the N-Gain test was 0.72 and the anacova test obtained a significance value of 0.017, this value is smaller than the critical sig (0.05). This shows that the simulation learning model affects the improvement of students' metacognitive skills and learning outcomes. The magnitude of the influence of the Simayang learning model is 77.5%. These results can be concluded that the Simayang learning model can affect the improvement of students' metacognitive skills on the atomic structure material. Keywords: Simayang learning model, metacognitive skills, atomic structure